Exploration the Mechanism of Doxorubicin-Induced Heart Failure in Rats by Integration of Proteomics and Metabolomics Data - Yuan, Yu; Fan, Simiao; Shu, Lexin; Huang, Wei; Xie, Lijuan; Bi, Chenghao; Yu, Hongxin; Wang, Yuming; Li, Yubo (Frontiers in Pharmacology, 2020)
Heart failure is currently a worldwide systemic disease with high morbidity and mortality and is very common. Doxorubicin (DOX) is a commonly used anthracycline broad-spectrum anti-tumor antibiotic with strong anti-tumor effect and definite curative effect. However, cardiotoxicity is the adverse reaction of drug dose cumulative toxicity, but the mechanism is still unclear. In this study, proteomics and metabonomics techniques were used to analyze the tissue and plasma of adriamycin-induced heart failure in rats, and to clarify the molecular mechanism of the harmful effects of DOX on cardiac metabolism and function in rats from a new point of view. The results showed that A total of 278 proteins with significant changes were identified by quantitative proteomic analysis, of which 118 proteins were significantly up-regulated and 160 proteins were significantly down-regulated in myocardial tissue. In the metabonomic analysis, 21 biomarkers such as L-Octanoylcarnitine, Alpha-Ketoglutarate, Glutamine, Creatine, Sphingosine and so on were detected. Correlation analysis showed that DOX-induced HF mainly affected Phenylalanine, tyrosine and tryptophan biosynthesis, D-Glutamine and D-glutamate metabolism, Phenylalanine metabolism, Biosynthesis of unsaturated fatty acids and other metabolic pathways, suggesting abnormal amino acid metabolism, fatty acid metabolism and glycerol phospholipid metabolism. It is worth noting that we have found the key upstream target of DOX-induced HF, PTP1B, which inhibits the expression of HIF-1α by inhibiting the phosphorylation of IRS, leading to disorders of fatty acid metabolism and glycolysis, which together with the decrease of Nrf2, SOD, Cytc and AK4 proteins lead to oxidative stress. Therefore, we think that PTP1B may play an important role in the development of heart failure induced by doxorubicin and can be used as a potential target for the treatment of heart failure.